Адсорбція антибіотиків макролідного ряду на високодисперсному кремнеземі - Slyshik, N. F.; Goncharik, V. P.; Kaspersky, V. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2004)
The adsorption of erithromycin and azithromycin on the high disperse silica has been examined as dependent on solution pH value and NaCl concentration. Maximum adsorption took place at pH 8–10. The results obtained testify an ionic mechanism of interaction of the protonated forms of antibiotics with dissociated silanol groups in weak basic solution and hydrogen bond formation in weak acidic one. The antibiotics studied are easily desorbed from silica surface with physiological solution (0,9 % NaCl) and are not desorbed practically with water.